Urogenital Abnormalities Associated to Anorectal Malformations and Hirschsprung’s Disease (London Journal of Medical and Health Research, 2025)
Introduction: The aim of this study was to establishthe correlation between urinary pathologies and anorectal malformationsand Hirschsprung’s disease andpresent their therapeutic particularities.Means and Methods: We retrospectively conducted a descriptive study at the Pediatric Surgery Department of the Queen Fabiola Children’s University Hospital (HUDERF) in Brussels. We got a clearanceconsent fromthe ethical committee of our hospital. During one month, we retrieved files of children who consulted for anorectal malformations and Hirschsprung’s diseases from August 1, 2011 to June 31, 2024. We Included all patients presenting Hirschsprung’s disease and those with upper anorectal malformations. We excludedpatients who presented lower anorectal malformations. Clinical parameters that we recorded included: age, sex, type of imaging, type of urinary abnormalityand treatment.Data were analyzed with Microsoft Office Excel 2010 and SPSS 2.0 software.Results:  We included 50 patients in our study; 16 cases of upper anorectal malformations and 34 cases of Hirschsprung’s disease. For radiologic assessments, 30 patients underwent abdominal ultrasound (US) and urethrocystography wasdone in 8 patients. Sevencases of urologic anomalies were associated to anorectal malformations 43.8%. The different urinary abnormalitiesfound were multicystic kidney (3 cases), vesicoureteral reflux(2 cases) and renal dysplasia (2 cases). Four cases of urologic malformations were associated toHirschsprung’s diseaseat least 11.8% (2 cases of megaureter and2 cases of hydronephrosis). The conservative treatment has been practiced associated to antibiotic prophylaxis in10 cases.Conclusion: This study is showing that urogenital abnormalitiesaremostly associated to anorectal malformations than Hirschsprung’s disease. In many casesthe treatment is conservative
Keywords: urogenital abnormality; anorectal malformation